2013
DOI: 10.1093/cercor/bht234
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms of Brain Plasticity with Complex Cognitive Training in Healthy Seniors

Abstract: Complex mental activity induces improvements in cognition, brain function, and structure in animals and young adults. It is not clear to what extent the aging brain is capable of such plasticity. This study expands previous evidence of generalized cognitive gains after mental training in healthy seniors. Using 3 MRI-based measurements, that is, arterial spin labeling MRI, functional connectivity, and diffusion tensor imaging, we examined brain changes across 3 time points pre, mid, and post training (12 weeks)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
199
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(236 citation statements)
references
References 54 publications
19
199
2
3
Order By: Relevance
“…As described by the investigators, “Skills addressed included higher-level cognitive strategies such as eliminating unimportant information (i.e., strategic attention), abstracting information in one’s own words (i.e., integrated reasoning), generating multiple interpretations and perspectives (i.e., elaborated reasoning), coming up with the personally applicable ‘take-home’ messages, and applying new learning to create novel individually relevant ideas (i.e., innovation)” (Cook, Chapman, Elliott, Evenson, & Vinton, 2014, p.4). This program demonstrated positive effects on gist reasoning among: adults with traumatic brain injury (Vas, Chapman, Cook, Elliott, & Keebler, 2011), adolescents with traumatic brain injury (Cook et al, 2014), and cognitively normal older adults (Anand, Chapman, Rackley, Keebler, Zientz, & Hart, 2011; Chapman et al, 2015). Chapman et al (2015) also found beneficial effects of treatment on cerebral blood flow and functional connectivity in the default mode and central executive networks.…”
Section: Resultsmentioning
confidence: 99%
“…As described by the investigators, “Skills addressed included higher-level cognitive strategies such as eliminating unimportant information (i.e., strategic attention), abstracting information in one’s own words (i.e., integrated reasoning), generating multiple interpretations and perspectives (i.e., elaborated reasoning), coming up with the personally applicable ‘take-home’ messages, and applying new learning to create novel individually relevant ideas (i.e., innovation)” (Cook, Chapman, Elliott, Evenson, & Vinton, 2014, p.4). This program demonstrated positive effects on gist reasoning among: adults with traumatic brain injury (Vas, Chapman, Cook, Elliott, & Keebler, 2011), adolescents with traumatic brain injury (Cook et al, 2014), and cognitively normal older adults (Anand, Chapman, Rackley, Keebler, Zientz, & Hart, 2011; Chapman et al, 2015). Chapman et al (2015) also found beneficial effects of treatment on cerebral blood flow and functional connectivity in the default mode and central executive networks.…”
Section: Resultsmentioning
confidence: 99%
“…(2012) suggested that changes in cerebrovasculature are a potential candidate mechanisms for gray matter changes following training, and Tak, Wang, Polimeni, Yan, and Chen (2014) reported a close association between the cerebrovasculature and measures of rsFC. Importantly, changes in cerebral blood flow and rsFC of the adult human brain following cognitive training have been previously reported (Chapman et al., 2015; Takeuchi et al., 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Attention training drills are grounded in the emerging literature supporting experience-dependent plasticity [16][17][18][19] and are mostly based on the adult brain injury rehabilitation literature that has produced practice guidelines supporting this intervention. 20,21 A critical issue with this intervention approach is equivocal evidence for generalization or "transfer" of gains from cognitive training to nontrained tasks, including everyday, "real-world" activities, in pediatric brain injury or other childhood conditions.…”
Section: The Treatment Evidence In Acquired Pediatric Brain Injurymentioning
confidence: 99%